Job Demands and Resources and Employee Well-Being in the Chinese Nonprofit Sector - Deng, Guosheng; Huang, Chienchung; Cheung, Shannon P.; Zhu, Shaoming (Frontiers in Psychology, 2021)
Although the nonprofit sector in China has grown substantially in past decades, its future is threatened by high turnover and burnout. It is thus necessary to investigate the factors that contribute to employee well-being (EWB) among nonprofit employees in China. This study used 233 foundation employees in China to examine the effects of job demands and resources (JD-R) on EWB. Estimates produced by regression analyses indicated that job resources (JR) have a strong effect on EWB (beta=0.53), as well as on the three EWB subscales (workplace, psychological, and life well-being). While job demands (JD) had no effects on overall well-being, they were negatively associated with workplace well-being (beta=-0.12). Robustness tests were conducted to further examine how JD and JR dimensions affect EWB and its subscales. Based on the findings, we underscore the importance of JR for EWB among foundation employees in China as well as that of implementing interventions that may alleviate the cost of emotional workload as a JD.